Keteladanan Akhlak Nabi Ibrahim AS: Kajian Terhadap Ayat-ayat Pesan Moral - Aulia, Firdaus (Tadabbur: Jurnal Peradaban Islam, 2020)
Alquran tells the stories of Prophet Ibrahim pbuh, whose contents are inseparable from moral messages. This study identifies the moral messages of verses on Prophet Ibrahim pbuhâ€™s; determine the relevance of verses on the Prophetâ€™s akhlaq with moral development in todayâ€™s society; and reveal the wisdom of stories about Prophet Ibrahim pbuhâ€™s exemplary akhlaq. The research method was qualitative, employed via the library research approach. Research data were analyzed using the analytical descriptive technique. The results showed there are three moral messages that can be gained from verses on Prophet Ibrahim pbuh. First, patience and resignation of self to Allah (QS. Al-á¹¢ÄfÄt ayat 99-113). Second, being gentle and preaching argumentatively without resorting to violence (QS. Maryam ayat 46-47 dan QS. Al-AnbiyÄâ€™ ayat 51-72). Third, submission and obedience to the commands of Allah (QS. Al-á¹¢ÄfÄt ayat 102). The moral messages contained in these verses are highly relevant to the moral development of a society. There are countless wisdoms that can be gained from stories of Prophet Ibrahim pbuhâ€™s akhlaq, but they can be reduced to seven points. First, faith and tawhid will create free and responsible individuals with good morals, trustworthy, and spread goodness. Second, encouraging oneself to think empirically. Third, patience and resignation when facing any calamities. Fourth, politeness and gentleness in spreading Islam. Fifth, persistence in attitude and effort to achieve the desired result or objective. Sixth, the story on sacrifice evokes mutual assistance in the society. Seventh, the story of Prophet Ibrahim pbuh also provides understanding on the power of supplication and effort.